Expected impact of applying new 2013 AHA/ACC cholesterol guidelines criteria on the recommended lipid target achievement after acute coronary syndromes. Issue 1 (March 2015) - Gencer, Baris; Auer, Reto; Nanchen, David; Räber, Lorenz; Klingenberg, Roland; Carballo, David; Blum, Manuel; Vogt, Pierre; Carballo, Sebastian; Meyer, Philippe; Matter, Christian M.; Windecker, Stephan; et al.
Abstract: Background: 2013 AHA/ACC guidelines on the treatment of cholesterol advised to tailor high-intensity statin after ACS, while previous ATP-III recommended titration of statin to reach low-density lipoprotein cholesterol (LDL-C) targets. We simulated the impact of this change of paradigm on the achievement of recommended targets. Methods: Among a prospective cohort study of consecutive patients hospitalized for ACS from 2009 to 2012 at four Swiss university hospitals, we analyzed 1602 patients who survived one year after recruitment. Targets based on the previous guidelines approach was defined as (1) achievement of LDL-C target < 1.8 mmol/l, (2) reduction of LDL-C ≥ 50% or (3) intensification of statin in patients who did not reach LDL-C targets. Targets based on the 2013 AHA/ACC guidelines approach was defined as the maximization of statin therapy at high-intensity in patients aged ≤75 years and moderate- or high-intensity statin in patients >75 years. Results: 1578 (99%) patients were prescribed statin at discharge, with 1120 (70%) at high-intensity. 1507 patients (94%) reported taking statin at one year, with 909 (57%) at high-intensity. Among 482 patients discharged with sub-maximal statin, intensification of statin was only observed in 109 patients (23%). 773 (47%) patients reached the previous LDL-C targets, while 1014 (63%) reached the 2013 AHA/ACC guidelines targetsone year after ACS (p value < 0.001). Conclusion: The application of the new 2013 AHA/ACC guidelines criteria would substantially increase the proportion of patients achieving recommended lipid targets one year after ACS. Clinical trial number, NCT01075868 . Highlights: New 2013 AHA/ACC cholesterol guidelines targets are easier to reach after ACS. Impact of new guidelines application on clinical outcomes is unknown after ACS. Intensification of statin therapy after hospital discharge is infrequent after ACS.